2018
DOI: 10.1039/c8nr05949g
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of clay nanotubes on hair surface for medical and cosmetic formulations

Abstract: While most hair care formulations are developed on the basis of surfactants or polymers, we introduce self-assembly coating of micro and nanoparticles as the underlying principle for hair modification, protection and enhancement. Halloysite clay nanotubes formed by rolled sheets of aluminosilicate kaolin assemble on the surface of hair forming a robust multilayer coverage. Prior to the application, clay nanotubes were loaded with selected dyes or drug allowing for hair coloring or medical treatment. This facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 41 publications
3
88
0
Order By: Relevance
“…Here we report our results, which allow for efficient labelling of halloysite with nucleic acids, thus expanding the use of halloysite in biotechnology. We also show the self-assembly of DNA-halloysite hybrids on surfaces, which may find applications in hair surface engineering [17].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Here we report our results, which allow for efficient labelling of halloysite with nucleic acids, thus expanding the use of halloysite in biotechnology. We also show the self-assembly of DNA-halloysite hybrids on surfaces, which may find applications in hair surface engineering [17].…”
Section: Introductionmentioning
confidence: 86%
“…It turned out to be an effective protector for orally administered DNA from stomach acidic environments and DNA-degrading enzymes, enabling a successful plasmid DNA delivery into mural small intestine cells [14]. DNA-binding properties of halloysite are not studied well so far, if compared with other clays, although halloysite nanotubes have already been reported as a promising drug and cosmetic carriers [4,[15][16][17] and successfully used for tissue engineering applications [18]. Halloysite nanotubes constitute a clay mineral with unique properties because of the oppositely charged outer and inner surfaces both of which can be used for binding various macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of selected dyes or drugs into HNTs prior to their application allows for hair coloring or medical treatment, respectively. 53 Recent in vivo studies confirmed the potential of HNTs as effective drug delivery containers, showing that treatment with curcumin-loaded HNTs suppresses the growth of pathogenic bacteria in C. elegans and completely restores the longevity of infected nematodes. 54 An in vivo study of pharmacokinetics revealed that an orally administered suspension of fluorescently labelled HNTs is not absorbed by the intestines and eliminated via feces within one day, while systemically administered nanotubes are eliminated via urine/feces within nearly 72 h. 55 Notably, although in this study and some other studies 23 HNTs are intravenously injected, HNTs are non-biodegradable in blood.…”
Section: Clay-based Nanomaterialsmentioning
confidence: 93%
“…In addition to CNTS, some other kinds of nanotubes, such as silica nanotubes, halloysite clay nanotubes, nickel vanadate nanotubes, and boron-nitride nanotubes, have also shown promise for haircare formulations owing to their toxic-free aqueous processing. Adding their abundant availability, low toxicity, biocompatibility, and low price, naturally occurring multipurpose nano clay nanotubes have gained incredible usage for haircare formulations [60][61][62].…”
Section: Nanotubes-based Formulations In Cosmeticsmentioning
confidence: 99%